2000
DOI: 10.1034/j.1600-051x.2000.027003149.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of tissue plasminogen activator (t‐PA) and plasminogen activator inhibitor 2(PAI‐2) in gingival crevicular fluid from healthy, gingivitis and periodontitis patients

Abstract: This study indicates that t-PA and PAI-2 may play a significant rôle in the periodontal tissue destruction and tissue remodeling and that t-PA and PAI-2 in GCF may be used as clinical markers to evaluate the periodontal diseases and assess treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 17 publications
0
42
1
Order By: Relevance
“…Increased levels of the plasminogen-activator-inhibitors were previously detected in inflammed gingival and periodontal tissues. 15,16 Our study showed a significant association between the carriage of the allele 4G (deletion) polymor-…”
Section: Discussionmentioning
confidence: 59%
“…Increased levels of the plasminogen-activator-inhibitors were previously detected in inflammed gingival and periodontal tissues. 15,16 Our study showed a significant association between the carriage of the allele 4G (deletion) polymor-…”
Section: Discussionmentioning
confidence: 59%
“…Because of very low levels, these results should be interpreted with caution. It is also reported that TNF-α is more present in active lesions [40,41]. In another study TNF-α was detected in 37 of 42 implant samples, but no correlations between the severity of peri-implant inflammation and the presence of TNF-α were found [13].…”
Section: Periodontitis and Peri-implantitismentioning
confidence: 98%
“…The alteration in the pattern of PA distribution, according to periodontal status, suggests that PA is involved in the periodontal homeostasis 58 . The levels of tPA and the plasminogen activator inhibitor-2 (PAI-2) are greater in gingival crevicular fluid of patients with periodontitis than in periodontally healthy patients 59 .…”
Section: Immunosenescence and Periodontal Cells Interactionmentioning
confidence: 99%